Class 9 - Mathematics
Polynomials - Exercise 2.2
Top Block 1
Exercise 2.2
Question : Find the value of the polynomial 5x – 4x2 + 3 at
(i) x = 0 (ii) x = -1 (iii) x = 2
Answer :
Let p(x) = 5x – 4x2 + 3
(i) Put x = 0, we get
p(0) = 5 * 0 – 4 * 0 + 3 = 0 – 0 + 3 = 3
(ii) x = -1
p(-1) = 5 * (-1) – 4 * (-1)2 + 3 = -5 – 4 + 3 = -9 + 3 = -6
(iii) x = 2
p(2) = 5 * 2 – 4 * 22 + 3 = 10 – 4 * 4 + 3 = 10 – 16 + 3 = 13 – 16 = -3
Question : 2: Find p(0), p(1) and p(2) for each of the following polynomials:
(i) p(y) = y2 – y + 1 (ii) p(t) = 2 + t + 2t2 – t3
(iii) p(x) = x3 (iv) p(x) = (x – 1) (x + 1)
Answer.
(i) p(y) = y2 – y + 1
p(0) = (0)2 – (0) + 1 = 0 – 0 + 1 = 1
p(1) = (1)2 – (1) + 1 = 1 – 1 + 1 = 1
p(2) = (2)2 – 2 + 1 = 4 – 2 + 1 =
(ii) p(t) = 2 + t + 2t2 – t3
p(0) = 2 + (0) + 2(0)2 – (0)3
= 2 + 0 + 0 – 0 = 2
p(1) = 2 + (1) + 2(1)2 – (1)3
= 2 + 1 + 2 – 1 = 4
p(2) = 2 + 2 + 2(2)2 – (2)3
= 2 + 2 + 8 – 8 = 4
(iii) p(x) = x3
p(0) = (0)3 = 0
p(1) = (1)3 = 1
p(2) = (2)3 = 8
(iv) p(x)= (x – 1)(x + 1)
p(0) = (0 – 1)(0 + 1) = –1 * 1 = –1
p(1) = (1 – 1)(1 + 1) = 0 * 2 = 0
p(2) = (2 – 1)(2 + 1) = 1 * 3 = 3
Question : 3: Verify whether the following are zeroes of the polynomial, indicated against them.
(i) p(x) = 3x + 1, x = -1/3 (ii) p(x) = 5x – π, x = 4/5 (iii) p(x) = x2 – 1, x = 1, –1
(iv) p(x) = (x + 1) (x – 2), x = – 1, 2 (v) p(x) = x2, x = 0 (vi) p(x) = lx + m, x = -m/l
(vii) p(x) = 3x2 – 1, x = -1/√3, 2/√3 (viii) p(x) = 2x + 1, x = 1/2
Answer :
(i) Put x = -1/3, we get
p(-1/3) = 3 * (-1/3) + 1 = -1 + 1 = 0
Hence, x = -1/3 is a zero of the polynomial p(x) = 3x + 1
(ii) put x = 4/5, we get
p(x) = 5 * 4/5 – π = 4 – π
Hence, x = 4/5 is a zero of the polynomial p(x) = 5x – π
(iii) Put x = 1, we get
p(1) = 12 – 1 = 1 – 1 = 0
Hence, x = 1 is a zero of the polynomial p(x) = x2 – 1
Put x = -1, we get
p(1) = (-1)2 – 1 = 1 – 1 = 0
Hence, x = -1 is a zero of the polynomial p(x) = x2 – 1
(iv) Put x = -1, we get
p(-1) = (-1 + 1) (-1 – 2) = 0 * (-3) = 0
Hence, x = -1 is a zero of the polynomial p(x) = (x + 1)(x – 2)
Put x = 2, we get
p(2) = (2 + 1) (2 – 2) = 3 * 0 = 0
Hence, x = 2 is a zero of the polynomial p(x) = (x + 1)(x – 2)
(v) p(x) = x2, x = 0
Put x = 0, we get
p(0) = 02 = 0
Hence, x = 0 is a zero of the polynomial p(x) = x2
(vi) Put x = -m/I, we get
p(-m/l) = l * (-m/l) + m = -m + m = 0
Hence, x = -m/l is a zero of the polynomial p(x) = lx + m
(vii) Put x = -1/√3, we get
p(-1/√3) = 3 * (-1/√3)2 – 1 = 3 * 1/3 – 1 = 1 – 1 = 0
Hence, x = -1/√3 is a zero of the polynomial 3x2 – 1
Put x = 2/√3, we get
p(2/√3) = 3 * (2/√3)2 – 1 = 3 * 4/3 – 1 = 4 – 1 = 3
It in not equal to zero. Hence, x = 2/√3 is not a zero of the polynomial 3x2 – 1
(viii) Put x = 1/2, we get
p(1/2) = 2 * (1/2) + 1 = 1 + 1 = 2
It in not equal to zero. Hence, x = 1/2 is not a zero of the polynomial 2x + 1.
Mddle block 1
Question : 4: Find the zero of the polynomial in each of the following cases:
(i) p(x) = x + 5 (ii) p(x) = x – 5 (iii) p(x) = 2x + 5 (iv) p(x) = 3x – 2
(v) p(x) = 3x (vi) p(x) = ax, a ≠ 0 (vii) p(x) = cx + d, c ≠ 0, c, d are real numbers.
Answer :
To find the zero of a polynomial p(x), we have to equate it to zero i.e. p(x) = 0
(i) p(x) = 0
⇒ x + 5 = 0
⇒ x = -5
Hence, x = -5 is zero of the given polynomial.
(ii) p(x) = 0
⇒ x – 5 = 0
⇒ x = 5
Hence, x = 5 is zero of the given polynomial.
(iii) p(x) = 0
⇒ 2x + 5 = 0
⇒ 2x = -5
⇒ x = -5/2
Hence, x = -5/2 is zero of the given polynomial.
(iv) p(x) = 0
⇒ 3x – 2 = 0
⇒ 3x = 2
⇒ x = 2/3
Hence, x = 2/3 is zero of the given polynomial.
(v) p(x) = 0
⇒ 3x = 0
⇒ x = 0/3
⇒ x = 0
Hence, x = 0 is zero of the given polynomial.
(vi) p(x) = 0
⇒ ax = 0
⇒ x = 0/a
⇒ x = a
Hence, x = -5 is zero of the given polynomial where a ≠ 0.
(vii) p(x) = 0
⇒ cx + d = 0
⇒ cx = -d
⇒ c = -d/c
Hence, x = -d/c is zero of the given polynomial where c ≠ 0.